The Use of Social Media by Local Governments: The Case of Manabí’s Cantons in Ecuador - Paiva Dias, Gonçalo (2020)
The use of social media as an instrument for public institutions to provide information and digital services to their citizens and promote their participation has become a common strategy in the scope of e-government. In this study, an empirical investigation of the diffusion of Facebook, Twitter, and YouTube among the local governments of the 22 cantons of the province of Manabí (Ecuador) is presented. In addition to portraying the adoption of social media by the local governments in the province, the results show that the Diffusion of Innovation (DOI) Theory can be used to explain the adoption process among the studied governments and that those can be classified according to the five DOI Theory’s adoption categories: innovators; early adopters; early majority; late majority; and laggards.